Validation of a high performance liquid chromatography method for quantification of urinary porphyrins (Revista Brasileira de Ciências Farmacêuticas, 2007)
Porphyrins are products that originate from the heme biosyntetic pathway. Enzymes that take part in this route can have their activity inhibited due to inherited/acquired or both factors resulting in increased serum heme precursor that will be eliminated in urine. Considering the importance of early detection of heme biosynthesis alterations, the purpose of this study was to establish a high pressure liquid chromatographic (HPLC) method with fluorescence detection, to detect five fractions of porphyrins: uroporphyrin (8-carboxyporphyrin), heptaporphyrin (7-carboxyporphyrin), hexaporphyrin (6-carboxyporphyrin), pentaporphyrin (5-carboxyporphyrin) and coproporphyrin I and III (4- carboxyporphyrin). Extraction methods with spectrophotometric detection are not sensitive enough for this purpose. The HPLC (Shimadzu Co., Kioto, Japan) was composed of two high-pressure pumps, auto-sampler and fluorescence detector (RF-535) with excitation at 400 nm and emission at 620 nm. The sample was eluted from a reversed-phase column with a linear gradient. The linearity of the method was from 8.0 to 120 µg/L for all fractions, proving its ablility to identify and quantify porphyrins with differents carboxylic groups for early diagnosis and follow-up of porphyrias.